Utilizing C. elegans Spermatogenesis and Fertilization Mutants as a Model for Human Disease - Sofia M. Perez; Helena S. Augustineli; Matthew R. Marcello (Journal of Developmental Biology)
The nematode C. elegans is a proven model for identifying genes involved in human disease, and the study of C. elegans reproduction, specifically spermatogenesis and fertilization, has led to significant contributions to our understanding of cellular function. Approximately 70 genes have been identified in C. elegans that control spermatogenesis and fertilization (spe and fer mutants). This review focuses on eight genes that have human orthologs with known pathogenic phenotypes. Using C. elegans to study these genes has led to critical developments in our understanding of protein domain function and human disease, including understanding the role of OTOF (the ortholog of C. elegans fer-1) in hearing loss, the contribution of the spe-39 ortholog VIPAS39 in vacuolar protein sorting, and the overlapping functions of spe-26 and KLHL10 in spermatogenesis. We discuss the cellular function of both the C. elegans genes and their human orthologs and the impact that C. elegans mutants and human variants have on cellular function and physiology. Utilizing C. elegans to understand the function of the genes reviewed here, and additional understudied and undiscovered genes, represents a unique opportunity to understand the function of variants that could lead to better disease diagnosis and clinical decision making.